Dental erosion in 12 to 16 years old school students using Basic Erosive Wear Examination (BEWE) index - Luis Angel Hayakawa Lastarria; Angie Gallo Oropeza; Leslie Casas-Apayco (Revista de Odontopediatria Latinoamericana)
Introduction: The aim of this study was to determine the prevalence and distribution of dental erosion in 12 to 16 year old students from “María Auxiliadora” public school at Chorrillos, Lima-Perú. Materials and methods: A total of 382 students were clinically exanimated for dental erosion using the Basic Erosive Wear Examination (BEWE). After the clinical examination, scores were obtained by sextants. They were then summed to produce in a accumulative score. The data was analyzed by descriptive statistics to relate the erosion with the sex and age. The Chi squared and Anova test (oneway) were used (p<0,05). Results: The prevalence of dental erosion was 12.04% and as to its distribution, the most representative age was the group of 16 years (28.26%), female were most frequent (54.3%), the predominant location was the lower maxilary (54.35%) posterior teeth (56.52%) oclusal surfaces (65%). Conclusions: Of the total number of students evaluated, 12.04% had dental erosion. A greater distribution of dental erosion in the female and in students of 16 years of age was found, but there was no statistical significance.